KETERKAITAN ANTARA LONELINESS DENGAN PENYESUAIAN DIRI PADA MAHASISWA RANTAU ASAL CIAMIS DI UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Sahra Dwi Mulya; Eka Rizki Meilani; Fatin Rohmah Nur Wahidah; Nia Anggri Noveni (CV. Denasya Smart Publisher, 2025)
This study aims to examine the correlation between loneliness and adjustment among students from Camis studying at Universitas Muhammadiyah Purwokerto. Migrant students often face various challenges, including feelings of loneliness, which may impact their ability to adapt to a new environment. Adjustment in this study refers to seven aspects based on Schneiders theory (1955), while loneliness is measured using the UCLA Loneliness Scale (Russell, 1996). A quantitative approach with a correlational method was employed. The sample consisted of 118 Clamis-origin migrant students selected through purposive sampling. The research instruments included a modified and validated adjustment scale and loneliness scale. Data were analyzed using Pearson correlation with the assistance of SPSS version 25. The results revealed a significant negative correlation between loneliness and adjustment among the migrant students, which indicates that the higher the level of loneliness experienced by the students, the lower their level of adjustment, and vice versa. These findings suggest that loneliness is an influential factor in the success of migrant students adjustment within the campus environment